ANALISIS HARGA POKOK PRODUKSI USAHA BUDIDAYA MAGGOT SEBAGAI PAKAN ALTERNATIF PERTUMBUHAN IKAN LELE - Arwita Irawati; Kurnia Ningsih (Jurnal Perikanan Pantura (JPP), 2024)
One of the problems that occurs is the production of artificial feed that is still imported so that the price of feed is relatively expensive and tends to increase, therefore the right solution is the manufacture of feed using local raw materials, one of which is maggot feed which is used as an alternative as artificial feed for catfish growth and suppresses feed prices. The purpose of this study is to determine the efficiency of production costs that occur by utilizing Black Soldier Fly larvae as an alternative feed for catfish for their growth. This research uses a hybrid approach between quantitative and qualitative with descriptive analysis and cost of goods produced by maggot cultivation. The data obtained in this study was processed using statistical formulas through the Microsoft Excel program. The calculation of cost of goods produced using the full costing method is carried out quantitatively and evaluates the growth of catfish by feeding dry maggots. The location of the research was carried out in CV. Millenial Agro Farm Jl. Toddopuli Raya Timur, Paropo Village, Panakukkang District, Makassar City. Cost of Goods Production of Dry Maggot as much as Rp. 99,789 in one cycle. The recommendation from the study is that the efficiency of the cost of goods produced can be done in several cycles.